Komunikasi Pemasaran Sarana Upakara Di Kawasan Pasar Tradisonal - Ni Made Ayu Sri Wulandari (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
This study try to explain the description of the marketing mix activities, barriers and implications of marketing communication activities. The aim is to analyze the importance and impact of marketing in the business world by traders to attract consumers so that traders do not suffer losses. The research approach is qualitative with the case study method and uses interview techniques, field observations, and documentation. The main sources consist of traders and consumers who buy ceremony facilities who are directly involved in marketing communication activities. The results of this study explain that traders select and carry out elements in the marketing mix to carry out marketing communications, including products, prices, promotions, locations. The marketing mix that is carried out by traders provides exposure to target markets effectively which has an impact on consumer awareness by making repeat buyers. Barriers that occur in marketing communication activities consist of language disorders, physical problems, and technical problems. The implications that occur in communication activities experience positive and negative impacts including the ease of obtaining the need for ceremonial facilities positively, but negatively resulting in the fading of the cultural values ​​of the tablejitan tradition in ceremonial preparation activities because they prefer to buy rather than make.